2007
DOI: 10.1021/jm0614883
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine-18-Labeled Benzamide Analogues for Imaging the σ2 Receptor Status of Solid Tumors with Positron Emission Tomography

Abstract: A series of fluorine-containing benzamide analogs was synthesized and evaluated as candidate ligands for positron emission tomography (PET) imaging of the sigma-2 (sigma2) receptor status of solid tumors. Four compounds having a moderate to high affinity for sigma2 receptors and a moderate to low affinity for sigma-1 (sigma1) receptors were radiolabeled with fluorine-18 via displacement of the corresponding mesylate precursor with [18F]fluoride. Biodistribution studies in female Balb/c mice bearing EMT-6 tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
130
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 100 publications
(132 citation statements)
references
References 19 publications
2
130
0
Order By: Relevance
“…Due to their modulative properties, s 1 ligands can be used for the treatment of psychosis [9], neuropathic pain [10], depressions [11], epilepsy [12] and Alzheimer's and Parkinson's Disease [13,14]. Furthermore, the development of radiolabeled s 1 and s 2 ligands as selective tumor imaging agents offers new chances for the diagnosis of tumors and their metastases [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their modulative properties, s 1 ligands can be used for the treatment of psychosis [9], neuropathic pain [10], depressions [11], epilepsy [12] and Alzheimer's and Parkinson's Disease [13,14]. Furthermore, the development of radiolabeled s 1 and s 2 ligands as selective tumor imaging agents offers new chances for the diagnosis of tumors and their metastases [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The most promising radiotracer reported to date-and the only s 2 -receptor-selective PET radiotracer to be used in human studies-is the conformationally flexible benzamide analog 2-(2-[ 18 F]fluoroethoxy)-N-(4-(3,4-dihydro-6,7-dimethoxyisoquinolin-2(1H)-yl)butyl)-5-methyl-benzamide ( 18 F-ISO-1). In vivo small-animal PET studies demonstrated that 18 F-ISO-1 imaged breast tumors in a rodent model of breast cancer (31). However, a key step in the validation of this radiotracer for imaging of the proliferative status of breast tumors was the demonstration of a good correlation between 18 F-ISO-1 uptake and the P:Q ratio of a panel of breast tumors.…”
Section: Smentioning
confidence: 99%
“…The follow-up studies showed one of the compounds, 4-(6,7-dimethoxy-3,4-dihydroisoquinolin-2(1H)-yl)-N-(2-(2-18 F-fluoroethoxy)-5-methylbenzyl)butan-1-amine ( 18 F-ISO-1) (Fig. 6), with binding affinity at the namomolar level at 2.8 nM, and the tumor-tonormal tissue ratio fell between 2 to 6 at 5 mins to 60 mins, which is suitable to develop into a radiotracer in clinical trials [145,146]. Therefore, these benzamide σ 2 receptor imaging agents may have potential for highly proliferative tumor imaging.…”
Section: Pet Probes For Imaging Somatostatin Receptorsmentioning
confidence: 99%